Manual de orientações para pacientes e familiares: transplante de fígado - Felício, Helen Catharine Camarero de (2007)
Liver transplantation is currently indicated for chronic and acute liver failure when no other treatment is available. As a complex procedure, it requires interdisciplinary care and the patients and caregivers´ compliance behavior. Objectives: to obtain from liver recipients, transplant candidates, families and health care professionals what kind of information they considered sufficient or insufficient about liver transplantation; to use the obtained data to elaborate a manual with information identified as relevant and necessary. Method: this is a descriptive study approved by the Ethics Committee and conducted at the Unity of Surgery and Liver and Large Intestine Transplant, Hospital de Base, Sao Jose do Rio Preto, S.P. A total of 50 liver transplant candidates , 50 caregivers of these patients , 50 recipient patients and 24 health care professionals from this unity comprised the study. All patients and caregivers were interviewed in the Outpatient Service and in the Transplant Unit by the research nurse. All professionals received a questionnaire; afterwards the answers were returned to the researcher. Results: Most patients were male: liver recipients (41 men; mean age: 47.52; sd: 11.7); candidate patients (30 men; mean age: 48.02; sd:10.29). The Group of caregivers (n: 37) and professionals (n: 15) comprised mostly women. Professional team comprised physicians, nurses, psychologists, social workers, nutritionists and physical therapists. Recipients related insufficient information (p<0.032) concerning their disease, exams, waiting list, pre- and postsurgery periods, immunosupressor drugs, rejection and complications and follow-up at the outpatient clinic. Candidate patients considered they had insufficient information (p<0.032) about their disease (liver functioning, cyrrhosis, severity and complications); about the treatment (exams and protocol); surgery (need for surgery and donor); pre-, intra and postoperative periods (hospital arrival, exams and procedures at the operating room, duration and risks of surgery and ICU) and follow-up (rejection, retransplantation, immunosupressors, diet and follow-up). Caregivers had insufficient information (p<0.032) about the disease, exams, treatment, waiting list, quality of life, hospitalization, protocol, pré-, intra e postoperative periods, immunosupressor drugs , rejection and complications, retransplantation, pre- and post diet, hospital discharge and outpatient follow-up. Professionals´ answers pointed out topics related to their own specialties . Conclusions: even thought all health care professionals provide information; patients and caregivers still report not to have enough information about the whole process of liver transplantation. An orientation manual was elaborated based on the obtained data.